A Narrative Review on the FSTL-1 Protein and its Current Known Impact on Cardiovascular Ischaemic Disease - Rodrigues Gomes, José (International Journal of Medical Students, 2024)
This narrative review investigates the potential therapeutic role of FSTL-1 in addressing severe cardiac issues following myocardial infarctions (MI). Despite advances in modern medicine, MI persist as a leading global cause of death, with stem cell therapy falling short of expectations since the early 2000s. In contrast, FSTL-1, an emerging bone morphogenetic protein, demonstrates promise based on successful studies. We conducted a qualitative narrative synthesis of studies published in PubMed, Scopus, and Web of Science between January 2000 and May 2022. This research explores the intricate scientific aspects of FSTL-1's contribution to myocardial regeneration, utilizing a chronological approach to trace its progression from biological pathways to broader scenarios. It examines the mechanisms regulated by FSTL-1 and its effects on cardiac tissue and cells, highlighting its potential as a therapeutic agent emphasizing its multifaceted role in cardiac regeneration. By deepening our comprehension of FSTL-1, this study significantly contributes to knowledge advancement, offering insights into its role in addressing severe cardiac issues post-MI. By consolidating current knowledge and proposing new avenues for investigation, this work offers valuable insights into FSTL-1's significance in advancing cardiovascular health and post-MI recovery.